Can we teach an old drug new tricks? - Ch'ng, J; Renia, L; Nosten, F; Tan, K (2012)
Although resistance to chloroquine (CQ) has relegated it from modern chemotherapeutic strategies to treat . Plasmodium falciparum malaria, new evidence suggests that higher doses of the drug may exert a different killing mechanism and offers this drug a new lease of life. Whereas the established antimalarial mechanisms of CQ are usually associated with nanomolar levels of the drug, micromolar levels of CQ trigger a distinct cell death pathway involving the permeabilization of the digestive vacuole of the parasite and a release of hydrolytic enzymes. In this paper, we propose that this pathway is a promising antimalarial strategy and suggest that revising the CQ treatment regimen may elevate blood drug levels to trigger this pathway without increasing the incidence of adverse reactions. © 2012 Elsevier Ltd.